Synthesis, characterization and unusual near-infrared luminescence of 1, 1, 4, 4-tetracyanobutadiene derivatives. Issue 24 (27th February 2020) - Bui, Anh Thy; Philippe, Clotilde; Beau, Maxime; Richy, Nicolas; Cordier, Marie; Roisnel, Thierry; Lemiègre, Loïc; Mongin, Olivier; Paul, Frédéric; Trolez, Yann
Abstract : Two 1, 1, 4, 4-tetracyanobutadiene (TCBD) derivatives were prepared by reaction of tetracyanoethylene with ynamides bearing either a pyrene or a perylene unit. They display luminescence that could be detected up to 1350 nm in the solid state. Abstract : Two 1, 1, 4, 4-tetracyanobutadiene (TCBD) derivatives were prepared by [2+2]cycloaddition–retroelectrocyclization from ynamides bearing either a pyrene (1 ) or a perylene unit (2 ). In addition to panchromatic absorptions in 2, in the solid state, both compounds unexpectedly display NIR photoluminescence that could be detected up to about 1350 nm.